Integrating Islamic Values in EFL Instruction: Developing Speaking for Formal Interactions Textbook in an Islamic University Context - Basori Basori; Nur Fitria Anggrisia; Harir Mubarok; Fitria Zulaika Mahfudza; Agwin Degaf (Universitas Pendidikan Ganesha, 2025)
The lack of culturally relevant instructional materials for EFL learners, particularly in integrating linguistic competence with Islamic values, remains a critical challenge. This study addresses this issue by developing and validating the Speaking for Formal Interactions textbook, designed to enhance linguistic proficiency and ethical communication skills. Conducted within the English Language Education Department at AKM Islamic University (pseudonym), the research involved second-semester undergraduate students. Using the ADDIE model as a framework, data collection employed a mixed-methods approach, including semi-structured interviews, questionnaires, and pre-tests and post-tests, with thematic analysis for qualitative data and statistical analysis for quantitative data. The findings revealed significant improvements in students’ speaking skills and confidence, with qualitative feedback emphasizing the textbook’s alignment with Islamic values such as adab (courtesy) and tabligh (clear communication). Expert reviewers commended the content’s scaffolding and cultural integration while recommending the inclusion of advanced digital tools for enhanced interactivity. This study extends the ADDIE framework to culturally responsive education, offering a replicable model for integrating linguistic, cultural, and ethical dimensions, with future iterations suggesting broader applications and digital enhancements to increase accessibility and engagement.